Effect of a cholesterol-rich diet on the metabolism of the free and esterified cholesterol components of a nanoemulsion that resembles LDL in rabbits - Padoveze,A.F. (2009)
We have shown that the free cholesterol (FC) and the cholesteryl ester (CE) moieties of a nanoemulsion with lipidic structure resembling low-density lipoproteins show distinct metabolic fate in subjects and that this may be related to the presence of dyslipidemia and atherosclerosis. The question was raised whether induction of hyperlipidemia and atherosclerosis in rabbits would affect the metabolic behavior of the two cholesterol forms. Male New Zealand rabbits aged 4-5 months were allocated to a control group (N = 17) fed regular chow and to a 1% cholesterol-fed group (N = 13) during a 2-month period. Subsequently, the nanoemulsion labeled with ³H-FC and 14C-CE was injected intravenously for the determination of plasma kinetics and tissue uptake of the radioactive labels. In controls, FC and CE had similar plasma kinetics (fractional clearance rate, FCR = 0.234 ± 0.056 and 0.170 ± 0.038 h-1, respectively; P = 0.065). In cholesterol-fed rabbits, the clearance of both labels was delayed and, as a remarkable feature, FC-FCR (0.089 ± 0.033 h-1) was considerably greater than CE-FCR (0.046 ± 0.010 h-1; P = 0.026). In the liver, the major nanoemulsion uptake site, uptake of the labels was similar in control animals (FC = 0.2256 ± 0.1475 and CE = 0.2135 ± 0.1580%/g) but in cholesterol-fed animals FC uptake (0.0890 ± 0.0319%/g) was greater than CE uptake (0.0595 ± 0.0207%/g; P < 0.05). Therefore, whereas in controls, FC and CE have similar metabolism, the induction of dyslipidemia and atherosclerosis resulted in dissociation of the two forms of cholesterol.